Understanding and creating biocementing beachrocks via biostimulation of indigenous microbial communities - Ramachandran, Asha; Polat, Pelin; Mukherjee, Abhijit; Dhami, Navdeep (SPRINGER, 2020)
Bacterially induced precipitation of minerals leading to cementation of natural geological formations has been well recorded in a variety of environments. A range of microbial pathways and geochemical processes have been found to influence the cementation processes; but detailed formation mechanisms and biogeochemical relationships are still not very clear. There has been a growing demand for the application of bacterially driven biocementation in a number of geotechnical engineering applications recently. Here, we aimed to unpin the mechanisms behind the formation of actively mineralising beachrock sediments at Lucky Bay in Western Australia to understand the natural accretionary processes and potential of indigenous bacterial communities in biocementation. We observed ferruginous, aluminosilicate and carbonate cements along with extensive extra polymeric substances, borings with possible microbial activities in certain sections of native beachrock sediments. Cement precipitation under calcium- and iron-rich microenvironments sourced from seawater and iron creek seems to be driven by both biogenic and abiogenic processes in nature. Native microbial communities with a dominance of the genera Halococcus and Marinobacter were recorded. Enrichment of native bacterial communities under seawater media conditions was conducted which lead to successful biomineralisation of calcitic and ferruginous cements under in vitro conditions although the community composition changed significantly. Nanomechanical properties of natural and laboratory synthesised cement crystals showed that engineered biocement is highly promising. The results of this study clearly demonstrate biological influence in the formation of natural cements and hint significant potential of biostimulation which can be harnessed for different engineering applications including coastal erosion.